Self-compassion in Haston’s Paperweight (2015): Its Ways and Effect for a Better Life - Arumdhani, Savira; Agustina, Mia Fitria; Utami, Shofi Mahmudah Budi (English Department, Faculty of Humanities, Andalas University, 2025)
The aim of this research is to find out the self-compassion depicted in Paperweight novel to overcome Stevie's bulimia nervosa. Paperweight by Meg Haston is a novel containing psychological issue related to eating disorder, bulimia nervosa, in Stevie as the main character. Stevie, who initially had suicidal thoughts because she felt neglected by her family and friends, eventually realized to recover from bulimia nervosa. Stevie’s realization to recover from bulimia is related with self-compassion because it is a component that reduces negative thoughts in someone with mental illness including bulimia nervosa. Then, in order to solve the problem, self-compassion theory by Neff (self-kindness, common humanity, mindfulness) is employed in this research. This research is qualitative research which was done subsequently by reading and rereading the novel, eliminating, identifying, and grouping, interpreting, describing, and analysing the data. In this research, the researchers found that Stevie possessed self-kindness to do treatment and she started doing fun things. Then, common humanity is found when Stevie realizes in this world every individual has his/her own problems. It is indicated that Stevie possessed mindfulness when she chose to leave an unpleasant memory and remember the pleasant one. As a result, self-compassion helps Stevie to recover from bulimia nervosa.